Final answer:
To evaluate the expression f(7/3) - h(-2), substitute the values of x in the functions f(x) and h(x), then subtract the result of h(-2) from f(7/3). The final result is 27.
Step-by-step explanation:
To evaluate the expression f(7/3) - h(-2), first substitute the value of x in the function f(x)
f(7/3) = 3(7/3) - 1 = 7 - 1 = 6
Next, substitute the value of x in the function h(x)
h(-2) = -2(-2)^2 + 3(-2) - 7 = -2(4) - 6 - 7 = -8 - 6 - 7 = -21
Finally, subtract h(-2) from f(7/3)
f(7/3) - h(-2) = 6 - (-21) = 6 + 21 = 27